Endocarditis associated with Comamonas acidovorans. - Horowitz, H (1990)
A case of endocarditis caused by Comamonas acidovorans (Pseudomonas acidovorans) in a 42-year-old intravenous-drug abuser is described. This article appears to be the first detailed report of the isolation of this organism from a systemic clinical infection and its identification as a pathogen.